PENELITIAN ANALISIS KEBUTUHAN PENGGUNA MELALUI DATABASE GOOGLE SCHOLAR: NARATIVE LITERATURE REVIEW - Rahman Muhammad Yusuf; Rully Khairul Anwar; Siti Chaerani Djen; Evi Nursanti Rukmana (BIBLIOTIKA : Jurnal Kajian Perpustakaan dan Informasi, 2023)
The problem of many unused library materials in a library may be due to the mismatch of the collection with the needs of library users. Some users are not satisfied with the library because the collection or information available in the library does not match what they want. So it is necessary to find out the needs of users so that all collections can be utilized properly by users because it suits their needs. The purpose of this research is to find out the analysis of user needs in the library. This research uses a narrative literature review method from references related to the topic of user needs analysis in libraries with a total of 10 references analyzed. Public libraries, national libraries, school libraries, college libraries, and special libraries will all be included in this study. The characteristics of library users differ depending on their information needs and background. In essence, the public are the main users of the library. People who utilize the library have a wide range of needs, including students, lecturers, teachers, staff, and the general public. User needs analysis activities conducted by libraries are done in various ways such as interviews, observations, case studies, and others. The community acts as the main user of the library. The community will assist the library in every user needs analysis activity. Therefore, the community will also determine the collections that must be in the library according to their respective information needs. This research will produce user needs analysis activities that have been carried out by various libraries with different users according to the type of library.Keyword:Analysis of user needs, collections, libraries